Design and development of hydrogel nanoparticles for mercaptopurine - V Senthil; R Suresh Kumar; C. V. V. Nagaraju; N Jawahar; G. N. K. Ganesh; K Gowthamarajan (Wolters Kluwer Medknow Publications, 2010)
Hydrogel nanoparticles have gained attention in recent years as they demonstrate the features and characters of hydrogels and nanoparticles at the same time. In the present study chitosan and carrageenan have been used, as hydrogel nanoparticles of mercaptopurine are developed using natural, biodegradable, and biocompatible polymers like chitosan and carrageenan. As these polymers are hydrophilic in nature, the particles will have a long life span in systemic circulation. Hydrogel nanoparticles with mercaptopurine is form an antileukemia drug by the counter polymer gelation method. Fourier-Transform Infrared (FT-IR) studies have shown a compatibility of polymers with the drug. The diameter of hydrogel nanoparticles was about 370 - 800 nm with a positive zeta potential of 26 - 30 mV. The hydrogel nanoparticles were almost spherical in shape, as revealed by scanning electron microscopy (SEM). Drug loading varied from 9 to 17%. Mercaptopurine released from the nanoparticles at the end of the twenty-fourth hour was about 69.48 - 76.52% at pH 7.4. The drug release from the formulation was following zero order kinetics, which was evident from the release kinetic studies and the mechanism of drug release was anomalous diffusion, which indicated that the drug release was controlled by more than one process.